Evolution of Reservation in India - Bansal, Arpana; Nath, Dr. Prem (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2010)
Reservation is a tool of increasing social diversity in organizations. It is one of the measures taken by the government to establish social justice. Reservation as a tool for socio-economic upliftment was adopted as a short-term measure for specific categories of people who for various reasons were discriminated against and deprived. This policy was adopted as the means to provide opportunities in employment. While the weaker sections should be given due opportunity, it is necessary to break the vicious circle of limited sections cornering the opportunities.